Impacts of an innovative credit + insurance bundle for marginalized farmers: Evidence from a cluster randomized trial in Odisha, India - Kramer, Berber; Pattnaik, Subhransu; Ward, Patrick S.; Xu, Yingchen (International Food Policy Research Institute, 2024)
Smallholder farmers often lack documented land rights to serve as collateral for formal loans, with livelihoods inextricably linked to weather conditions. Resulting credit and risk constraints prevent them from investing in their farms. We implemented a randomized evaluation of KhetScore, an innovative credit scoring approach that uses remote sensing to unlock credit and insurance for smallholders including landless farmers in Odisha, a state in eastern India. In our treatment group, where we offered KhetScore loans and insurance, farmers - and especially women - were more likely to be insured and borrow from formal sources without substituting formal for informal loans. Despite increased borrowing, treated households faced less difficulty in repaying loans, suggesting that insured KhetScore loans transferred risk and eased the burden of repayment. Moreover, the treatment enhanced agricultural profitability by increasing revenues during the monsoon season and reducing costs in the dry season. Positive and significant effects are found among both farmers with unconstrained baseline credit access, and quantity rationed farmers, suggesting that KhetScore helps address supply-side credit constraints. Finally, the treatment significantly enhanced women’s empowerment and mental health. In conclusion, remote sensing-enabled financial products can substantially improve landless farmers’ access to agricultural credit, risk management, resilience, and well-being.